Problematika Pengaturan Organisasi Sayap Partai di Indonesia - Zahri, Muhammad Riyanto (Jurist-Diction, 2021)
Abstract Every political party tries to maximize every component in the structure of their political party. One component that is in direct contact with the citizen is the wings of political parties, which is an important element in political parties to develop strategic political party programs that are indirectly not covered by political parties. There is an urgency to organize the wings of political parties as a form of the constitutional responsibility of the State for the right to associate and assemble of their own citizen; so that there is certainty to provide legal protection; and clarifying the socio-political status compared to other organizations. This article uses normative approach. The normative approach will be conducted by reviewing the Laws on specific issue of political party. Article show that there is an urgency to reform the model of constitutional legal regulations for WPP by making a special chapter on WPP and recommendations for the content of the ideal regulations for WPP. Keywords: Arrangement; Wings of Political Parties; Political Parties. Abstrak Setiap partai politik berusaha untuk memaksimalkan tiap-tiap komponen yang ada dalam struktur partainya. Salah satu komponen yang bersentuhan secara langsung dengan masyarakat adalah organisasi sayap partai, yang menjadi elemen penting dalam partai politik untuk mengembangkan program partai politik yang strategis yang secara tidak langsung dapat dicover oleh partai politik. Adanya urgensi untuk melakukan pengaturan organisasi sayap partai sebagai wujud tanggung jawab konstitusional Negara terhadap hak berserikat dan berkumpul warga negara; agar ada kepastian untuk memberikan perlindungan hukum; dan memperjelas status sosial-politik dibanding organisasi lainnya. Artikel ini menggunakan pendekatan normatif yaitu merujuk pada peraturan perundang-undangan yang berkaitan dengan partai politik. Artikel ini menunjukkan adanya urgensi untuk pembenahan model pengaturan hukum yang konstitusional terhadap OSP dengan membuat satu bab khusus tentang OSP dan rekomendasi muatan materi pengaturan yang ideal terhadap OSP. Kata Kunci: Pengaturan; Organisasi Sayap Partai; Partai Politik.